Enhanced cortisol secretion in acute transient global amnesia - Griebe, Martin; Ebert, Anne; Nees, Frauke; Gerber, Benjamin; Szabo, Kristina (Psychoneuroendocrinology, 2019)
Introduction - Stress-related transient inhibition of memory formation in the hippocampus has been hypothesized as one of the underlying pathomechanisms of transient global amnesia (TGA). TGA episodes, during which patients cannot encode and recall new information (anterograde amnesia affecting episodic long-term memory), are frequently preceded by a psychologically or physically stressful event. - Methods - We measured salivary cortisol during acute TGA in 14 patients, as well as cortisol day-profiles and the effect of experimental exposure to stress (using the socially evaluated cold pressor test) on cortisol levels during the subacute phase. We assessed psychiatric comorbidity as well as depression, trait anxiety and chronic stress. These findings were compared with data of 20 healthy controls. - Findings - Nine patients reported a precipitating stressor and all 14 developed typical hippocampal lesions on follow-up MRI. During TGA, salivary cortisol levels were more than 3-fold higher compared to time-matched day levels. While there was no difference in mean cortisol levels of the diurnal rhythm, we found a significant interaction between groups during experimental stress exposure (p = 0.049) with the TGA group revealing a higher cortisol increase. The TGA group reported higher levels of depressive symptomatology (CES-D) and higher scores of chronic stress (TICS) compared with the control group and there was a significant correlation between cortisol increase during TGA and the results of self-rating according to the CES-D (r = 0.615; p = 0.004), as well as to the STAI (r = 0.702; p = 0.001). - Conclusion - Our findings of enhanced secretion of cortisol in acute TGA patients correlating with symptoms of depression and anxiety and a persisting hyperreactivity to experimental stress in the subacute phase support the hypothesis that stress might be significant for the pathogenesis of TGA.
Available online 25 August 2018
Gesehen am 15.05.2019